DWELLING FIRE SAFETY EVACUATION (DFSE): A SYSTEMATIC REVIEW - Abdul Aziz, Nurul Ayuni; Mohd Nordin, Rumaizah; Ismail, Zulhabri; Yunus, Julitta; Hashim, Norfashiha (Journal of Surveying, Construction and Property, 2020)
Fire is an ignition of heat and smoke materials, which can pose a significant life and property threat. Residential fire in Malaysia has a high percentage of fire cases due to electrical sources, cooking appliances, defective of equipment, careless and negligence. Evacuation during fire is the most critical features in building safety. This includes the utilization of Building Information Modelling (BIM) in developing a good and efficient fire evacuation. This research paper aims to propose and established a conceptual framework of Dwelling Fire Safety Evacuation (DFSE). This paper utilizes the technique of systematic overview from previous research which includes journals, conferences proceedings, reports, framework and guidelines. The outcome of this paper consists the elements of dwelling fire safety evacuation including the element of Fire Scenarios (i.e., Fire characteristic, Building characteristic and Occupant characteristic), Influences Perceived Risk (i.e., Individual-Based, Physical and Social), Survival Strategy (i.e., extinguish, shelter and evacuation) and Safety (i.e., shortest time and awareness) which contributed to the development of the conceptual framework. These findings will assist the extended investigation of DFSE for accidental fire situations.